The varied roles of pilA-N, omcE, omcS, omcT, and omcZ in extracellular electron transfer by Geobacter sulfurreducens - Jiang, Jie; He, Pengchen; Luo, Ying; Peng, Zhaofeng; Jiang, Yongguang; Hu, Yidan; Qi, Lei; Dong, Xiuzhu; Dong, Yiran; Shi, Liang (Frontiers in Microbiology, 2023)
Geobacter sulfurreducens mediates extracellular electron transfer (EET) reactions with different substrates, such as solid-phase Fe(III)-containing minerals, anodes and the cells of Geobacter metallireducens. To compare their roles in EET, the pilA-N, omcE, omcS, omcT and omcZ genes of G. sulfurreducens were systematically deleted. All mutants showed impaired and varied ability to form biofilms on nonconductive surface. Deletion of omcE also impaired bacterial ability to reduce ferrihydrite, but its impacts on the ability for anode reduction and the co-culture of G. metallireducens-G. sulfurreducens were minimal. The mutant without omcS showed diminished ability to reduce ferrihydrite and to form the co-culture, but was able to regain its ability to reduce anodes. Deletion of omcT, omcZ or pilA-N alone impaired bacterial ability to reduce ferrihydrite and anodes and to form the co-culture. Deletion of all tested genes abolished bacterial ability to reduce ferrihydrite and anodes. Triple-deletion of all omcS, omcT and omcZ abolished the ability of G. sulfurreducens to co-culture with G. metallireducens. However, deletion of only omcZ or pilA-N or both omcS and omcT abolished the ability of G. sulfurreducens without hydrogenase gene hybL to co-culture with G. metallireducens, which show their indispensable roles in direct electron transfer from G. metallireducens to G. sulfurreducens. Thus, the roles of pilA-N, omcE, omcS, omcT and omcZ for G. sulfurreducens in EET vary substantially, which also suggest that possession of PilA-N and multiple cytochromes of different structures enables G. sulfurreducens to mediate EET reactions efficiently with substrates of different properties.